Correlation of Lymph Node Density and Recurrence in Carcinoma Penis: A Perspective on Optimal Management and Unmet Needs from a Tertiary Care Centre (Global Journal of Medical Research, 2018)
Introduction: Penile carcinoma is a devastating urological neoplasm in which the most assertive prognostic variable is the presence of lymph node involvement. Multiple studies in the current literature have shown that the number of positive lymph nodes predict recurrence free survival (RFS) and overall survival (OS). The objective of this present retrospective analysis is to authenticate the use of LND as a predictor of RFS and OS after ILND. Methods: Our institutional penile cancer database was analyzed for patients who underwent ILND from January 2000 to May 2008. Survival analysis was performed using the Kaplan-Meier method to determine RFS and OS. Two-sided p values
Keywords: inguinal lymph node dissection; lymph node density; squamous cell carcinoma penis; overall survival; recurrence free survival; penectomy